Neural Dynamics of Improved Bimodal Attention and Working Memory in Musically Trained Children - Kausel, Leonie; Zamorano, Francisco; Billeke, Pablo; Sutherland, Mary E.; Larrain-Valenzuela, Josefina; Stecher, Ximena; Schlaug, Gottfried; Aboitiz, Francisco (Frontiers in Neuroscience, 2020)
Attention and working memory (WM) are core components of executive functions, and they can be enhanced by training. One activity that has shown to improve executive functions is musical training, but the brain networks underlying these improvements are not well known. We aimed to identify these networks in children who regularly learn and play a musical instrument using fMRI. Girls and boys aged 10 to 13 with and without musical training completed an attention and WM task while their brain activity was measured with fMRI. Participants were presented with a pair of bimodal stimuli (auditory and visual) and were asked to pay attention only to the auditory, only to the visual, or to both at the same time. The stimuli were afterwards tested with a memory task in order to confirm attention allocation. Both groups had higher accuracy on items that they were instructed to attend, but musicians had an overall better performance on both memory tasks across attention conditions. In line with this, musicians showed higher activation than controls in cognitive control regions such as the fronto-parietal control network during all encoding phases. In addition, facilitated encoding of auditory stimuli in musicians was positively correlated with years of training and higher activity in the left inferior frontal gyrus and the left supramarginal gyrus, structures that support the phonological loop. Taken together, our results elucidate the neural dynamics that underly improved bimodal attention and WM of musically trained children and contribute new knowledge to this model of brain plasticity.